Appraisal of anti-gout potential of colchicine-loaded chitosan nanoparticle gel in uric acid-induced gout animal model. (4th March 2022) - Parashar, Poonam; Mazhar, Ifrah; Kanoujia, Jovita; Yadav, Abhishek; Kumar, Pranesh; Saraf, Shubhini A.; Saha, Sudipta
Abstract: Present study is aimed at transdermal delivery of colchicine-loaded chitosan nanoparticles. The nanoformulations were prepared utilising spontaneous emulsification method and optimised through 2 3 factorial designs. The optimised formulation (CHNP-OPT) displayed an average particle size of 294 ± 3.75 nm, entrapment efficiency 92.89 ± 1.1% and drug content 83.45 ± 2.5%, respectively. In vitro release study demonstrated 89.34 ± 2.90% release over a period of 24 h. Further, CHNP-OPT incorporated into HPMC-E4M (hydroxypropyl methylcellulose) to form transdermal gel. CHNPgel displayed 74.65 ± 1.90% permeation and stability over a period of 90 days. The anti-gout potential of CHNPgel formulation was evaluated in vivo against monosodium urate (MSU) crystal-induced gout in animal model. There was significant reduction in uric acid level, during MSU administration, when compared with the conventional gel of colchicine. The enhanced therapeutic potential was witnessed through X-ray. The study revealed that colchicine-loaded CHNPgel proved their supremacy over plain colchicine and can be an efficient delivery system for gout treatment.